Inuktitut Syllabics and Microcomputers - Hitch, Doug (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractWord processing with Syllables is now very common. Many different approaches have been used. In 1985 a computer code standard like the ASCII was proposed for Syllables in order to facilitate communication. This has not been widely implemented and is not likely to gain further recognition. Macintosh computers have always had a built-in ability to show Syllables on the screen. DOS computers have employed various technologies to do this. For both types of computers there are Syllables word-processing solutions that employ the proposed standard and those that do not. Today the Macintosh is the machine of choice for work with Syllables. Three different strategies are currently in use with the Macintosh, involving a keyboard translator, over-striking, or Option key. There are four outline fonts for the Mac on the market. Two organizations, the ISO and Unicode, inc., are working on a new computer code which will contain more than 65,000 characters. Syllables should be included in this set. It would be useful to standardize the Syllables keyboard. There are different key layouts for almost every solution. A standard layout for Syllables, like that for English, will probably survive through several generations of technological change.